Woorkout2
Rozwiązane

Zapisz w najprostszej postaci:



Zapisz W Najprostszej Postaci class=

Odpowiedź :

[tex]a) \ (8x^{5}+6x^{4}+3)+(-8x^{5}-5x^{4}+x-3) =8x^{5}+6x^{4}+3-8x^{5}-5x^{4}+x-3 =\\\\= 8x^{5}-8x^{5}{+6x^{4}-5x^{4}+x+3-3} = x^{4}+x[/tex]

[tex]b) \ (2x^{3}-11x^{2}+12x)-(x^{2}-10x+3) =2x^{3}-11x^{2}+12x-x^{2}+10x-3=\\\\=2x^{3}-11x^{2}-x^{2}+12x+10x-3 = 2x^{3}-12x^{2}+22x-3[/tex]

[tex]c) \ (5x^{2}+3)(3x^{2}+4x-2) = 15x^{4}+20x^{3}-10x^{2}+9x^{2}+12x-6=\\\\=15x^{4}+20x^{3}-x^{2}+12x-6[/tex]

Szczegółowe wyjaśnienie:

[tex]a)\ (8x^5+6x^4+3)+(-8x^5-5x^4+x-3)\\=8x^5+6x^4+3+-8x^5-5x^4+x-3\\=(8x^5-8x^5)+(6x^4-5x^4)+x+(3-3)\\=\huge\boxed{x^4+x}[/tex]

[tex]b)\ (2x^3-11x^2+12x)-(x^2-10x+3)\\=2x^3-11x^2+12x-x^2+10x-3\\=2x^3+(-11x^2-x^2)+(12x+10x)-3\\=\huge\boxed{2x^3-12x^2+22x-3}[/tex]

[tex]c) (5x^2+3)(3x^2+4x-2)\\=(5x^2)(3x^2)+(5x^2)(4x)+(5x^2)(-2)+(3)(3x^2)+(3)(4x)+(3)(-2)\\=15x^4+20x^3-10x^2+9x^2+12x-6\\=15x^4+20x^3+(-10x^2+9x^2)+12x-6\\=\huge\boxed{15x^4+20x^3-x^2+12x-6}[/tex]